Digital Manufacturing Deployment in Contemporary Supply Chains: A Case Study Approach - Jimo, Ajeseun L. (2016)
Purpose - The purpose of this paper is to understand Direct Digital Manufacturing deployment practices of firms in two different industries (aerospace and retail) and the corresponding relationships between the technology capabilities and operations performance objectives at different levels in the operation. Design Methodology - A multiple qualitative case-based research methodology is employed. DDM examples from the two case industries are analysed and compared along a specific set of dimensions to establish similarities and differences for theory development, generalization and articulation of research agendas. Findings - Amongst the results produced was the provision of a mapping of DDM configurations based on product and market characteristics and the identification of relationships between some constructs such as industry regulation, process technology and capacity deployment, amongst others. Research Limitations - The limitation of the research is in the use of secondary data with is limited in detail. Practical Implications - The framework developed can serve as a potential guide to operations managers in firms intending to deploy DDM. Originality/Value - This Study is the first to develop a framework for analysing DDM operations at the process and supply chain level. It is also the first to provide a classification system for DDM products based on process and supply chain level configuration.